REDUPLIKASI DALAM CERITA RAKYAT MELAYU RIAU - Wulandari Kusumawardani; Mangatur Sinaga; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is titled reduplication in Riau Malay Folklore. The purpose of this study is to identify forms and meanings of reduplication in Riau Malay Folklore. The benefits of this research are divided into two namely practical and theoretical. The operational definition is research that directs to the forms and meanings of reduplication contained in Riau Malay Folklore which in this case is focused on reduplication contained in the Riau Malay Folklore book from Bengkalis Regency entitled: Khayal Interview with Yung Dollah, Lancang Kuning in Bukit Batu, Dedap Durhaka, Awang Pink Crushing Lanun, Story of the Terubuk King Falling in Love with Princess Puyu, A Brief History of Datuk Setia Indra Merbau, Tragedy in Tanah Pereban, and Panglima Bujang Kelana. The data of this study are the contents of the Riau Malay Folk Stories, especially those from Bengkalis Regency, where there is a re-use or reduplication in the Riau Malay Folklore book, especially those from Bengkalis Regency. The research method used is a qualitative method that describes descriptive data. Data collection techniques used are reading and note-taking techniques. After the data is collected, the steps or techniques used in analyzing the data are as follows: (1) identifying reduplication contained in the Malay folklore book especially those from Bengkalis Regency, (2) grouping the forms and meanings of reduplication contained in the Riau Malay Folklore book especially those from Bengkalis Regency. (3) describe the forms and meanings of reduplication obtained in the Riau Malay Folklore book especially those from Bengkalis Regency, (4) conclude how the forms and meanings of reduplication contained in the Riau Malay Folklore book especially those originating from Bengkalis Regency. Based on the data analysis that has been done, found 226 reduplication data in Riau Malay Folklore. Key Words: Reduplication, Forms of Reduplication, Meaning Reduplication, Riau Malay Folklore